1997
DOI: 10.1088/0953-8984/9/2/019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure on the electronic states of FeS and studied by Mössbauer spectroscopy

Abstract: We have measured under pressure Mössbauer spectra of FeS and 3c-type up to 16 GPa and x-ray diffraction patterns of up to 11 GPa at room temperature. It is found for that the compressibilities of the lattice parameters exhibit definite anomalies at around 4.5 GPa and that there is no change in the crystal structure up to 11 GPa. Magnetically ordered Mössbauer spectra are observed below 6.5 GPa for FeS and 4.5 GPa for , whereas the spectra above these pressures are typical of a paramagnetic ordering with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
42
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 16 publications
11
42
3
Order By: Relevance
“…A reversible electronic transition in FeS is closely related to the structural transition from a manganese phosphide-like phase to a monoclinic phase, with no sign of metallization at the transition [504]. The XES result is consistent with the disappearance of the magnetic splitting from Mössbauer spectroscopy [505]. Late transition metal oxides (MnO, FeO, CoO) are typical Mott insulators of charge-transfer type (U<).…”
Section: Spin-pairingsupporting
confidence: 58%
“…A reversible electronic transition in FeS is closely related to the structural transition from a manganese phosphide-like phase to a monoclinic phase, with no sign of metallization at the transition [504]. The XES result is consistent with the disappearance of the magnetic splitting from Mössbauer spectroscopy [505]. Late transition metal oxides (MnO, FeO, CoO) are typical Mott insulators of charge-transfer type (U<).…”
Section: Spin-pairingsupporting
confidence: 58%
“…[1,21,22] However, there is an alternative scenario, which implies gradual metalization under pressure and the loss of the magnetic moments. [17,23] The absence of long range magnetic order in the high-pressure phase can be explained by electron delocalization: the increase of pressure results in the band broadening and in breaking of the Stoner criterion.…”
Section: +mentioning
confidence: 99%
“…[10] An abrupt breaking of long range magnetic order at room temperature is observed above 6.7 GPa. [10,16,17] This transition is accompanied by lattice volume collapse [6] and a change in the crystal symmetry (space group P 2 1 /a). The effective magnetic moment in Curie-Weiss theory, µ ef f , of FeS at ambient pressure is 5.5µ B .…”
Section: Introductionmentioning
confidence: 99%
“…In a simple metal, there also exist interactions connecting a large number of ions in addition to this force because of a nonlocal electron ion potential. The measurement of 57 Fe Mössbauer spectra was carried out under pressure [19]. It was found that the pressure dependence of the center shift changes significantly at 6.5 GPa.…”
mentioning
confidence: 99%